2021
DOI: 10.1002/ente.202100769
|View full text |Cite
|
Sign up to set email alerts
|

Electrochromism or Water Splitting in Neutral Aqueous Solutions by a Metallo‐Organic Assembly

Abstract: Herein, two different functionalities of one metallo‐organic film assembled on the surface of a transparent metal‐oxide electrode are described. Two redox‐active elements, electrochromic iron–polypyridyl complexes and catalytically active palladium centers, operate by applying different potentials in aqueous solutions. The color of the material can be cycled 1500 times from dark purple to colorless by electrochemically addressing the Fe2+/3+ centers at 0.0–1.0 V (vs Ag/Ag+). The differences between the transmi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…Electrochromic (EC) materials and electrochromic devices (ECDs) that show reversible color change upon application of a voltage have been widely used in a number of commercial and military applications, including energy-saving smart windows, flexible displays, , e-papers, , protective eyewear, , security, , energy storage devices, camouflage, and so on. In the past few decades, various types of materials have been established as EC materials, which can be classified into inorganic EC materials (various transition-metal oxides), organic EC materials (organic small molecules and polymers), and organic–inorganic hybrid EC materials (various metal–organic systems). Metallo-supramolecular polymers (MSPs) are generally considered as organic–inorganic hybrid EC materials because these polymers are typically synthesized by 1:1 complexation between organic ligands and metal ions. ,, Since Higuchi et al demonstrated the EC color change of MSP prepared from 1,4-bis­(2,2′:6′,2″-terpyridine-4′-yl)-benzene as a ditopic ligand and the Fe­(II) ion as the metal ion, many MSPs have been developed using bisterpyridine ligands and various metal ions like Fe 2+ , Co 2+ , Ru 2+ , Os 2+ , Cu 2+ , and so forth. , These monometallic MSPs have attracted great research attention for EC applications because of their interesting physical and optoelectronic properties like solution processability, high color contrast, fast response times, good coloration efficiency, and high durability.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic (EC) materials and electrochromic devices (ECDs) that show reversible color change upon application of a voltage have been widely used in a number of commercial and military applications, including energy-saving smart windows, flexible displays, , e-papers, , protective eyewear, , security, , energy storage devices, camouflage, and so on. In the past few decades, various types of materials have been established as EC materials, which can be classified into inorganic EC materials (various transition-metal oxides), organic EC materials (organic small molecules and polymers), and organic–inorganic hybrid EC materials (various metal–organic systems). Metallo-supramolecular polymers (MSPs) are generally considered as organic–inorganic hybrid EC materials because these polymers are typically synthesized by 1:1 complexation between organic ligands and metal ions. ,, Since Higuchi et al demonstrated the EC color change of MSP prepared from 1,4-bis­(2,2′:6′,2″-terpyridine-4′-yl)-benzene as a ditopic ligand and the Fe­(II) ion as the metal ion, many MSPs have been developed using bisterpyridine ligands and various metal ions like Fe 2+ , Co 2+ , Ru 2+ , Os 2+ , Cu 2+ , and so forth. , These monometallic MSPs have attracted great research attention for EC applications because of their interesting physical and optoelectronic properties like solution processability, high color contrast, fast response times, good coloration efficiency, and high durability.…”
Section: Introductionmentioning
confidence: 99%